Perinatal features and umbilical cord blood gases in newborns complicated with nuchal cord - Önderoğlu, Lütfü S.; Dursun, Polat; Durukan, Tekin (The Turkish Journal of Pediatrics, 2008)
Presence of nuchal cord (NC) is associated with transient decrease of umbilical cord blood flow. However, the exact perinatal effect of presence of NC in a newborn is still under debate. The aim of this study was to evaluate the perinatal complications and umbilical cord blood gases of deliveries complicated with NC and summarize the associated literature. Gestational age-matched term singleton pregnancies complicated with NC (n=160) were compared with neonates without NC (n=160). Patients' files and Labor and Delivery Unit database were used to extract maternal age, gestational age, presence of NC, number of nuchal loops around fetal neck, intrapartum complications and umbilical cord blood gases. pH, pO2, pCO2, HCO3-, O2 saturation, and base excess were determined in all patients. Mean maternal age, mean gestational age, and birth weight were not significantly different between the two groups (p > 0.05). Occurrence of oligohydramnios, intrauterine growth retardation (IUGR), intrapartum abnormalities and Apgar scores < 7 at 1 minute were not significantly different between the groups (p>0.05). However, umbilical cord blood pH (7.32 vs. 7.30, p = 0.048), pO2 (37.4 +/- 18.1 vs. 31.7 +/- 14.4, p = 0.01) and O2 saturation (57.4 +/- 21.8 vs. 48.3 +/- 20.4, p = 0.005) were significantly lower in the NC group compared with the controls. Furthermore, the number of Apgar scores < 7 at 1 minute was significantly higher in neonates with multiple NC (28.1% vs. 9.2%, p = 0.007), and intrapartum abnormalities were more frequently seen in newborns with multiple NC (31.3% vs.15.6%, p = 0.04). The results of this study suggest that presence of single NC may negatively affect the umbilical cord blood gases without significant perinatal complications. However, multiple NC may also increase the development of intrapartum complications and lower Apgar scores. Perinatal effects of NC should be investigated with a large prospective study.